Entangling and Elevating Creativity and Criticality in Participatory Futuring Engagements - Nicolas A. Balcom Raleigh; Sirkka Heinonen (Sage, 2025)
This article proposes that creativity and criticality not only can but should be entangled and elevated in participatory futuring engagements. Selected concepts from creativity theory and critical futures studies are applied to develop a set of futuring games through action research. We claim that participatory processes designed to entangle and elevate creativity and criticality produce more novel and varied ideas that better fit the purposes of futures studies. This article offers four arguments for combining creativity and criticality in participatory futuring engagements. First, due to complexity and uncertainty, the future is ultimately unknowable and requires tools to probe the unknown. Second, novelty is difficult to achieve in practice while creativity and criticality can help overcome these challenges. Third, discontinuities are the main sources of futures that are most radically different from the present and will have the biggest impact. Fourth, creativity and criticality support the rigorous imagining required for exploring and discovering new possible futures. This article analyzes three experimentations in entangling and elevating creativity and criticality in game-based futuring, stemming from Causal Layered Analysis. Based on these examples, we demonstrate that creativity and criticality, when combined, help people break through the limitations of current understanding, reveal approaching tipping points, and find the “unvisited cavities” through rhizomatic knowledge creation. However, there remain challenges in evaluating how well various participatory designs support creativity and criticality in practice. Context-sensitive evaluation tools and open sharing of outcomes are needed to develop participation design principles capable of supporting creativity and criticality in participatory futuring.